The effect of curcumin encapsulation into yeast glucan particles on antioxidant enzyme expression in vitro. Issue 5 (2nd February 2021) - Treml, Jakub; Šalamúnová, Petra; Hanuš, Jaroslav; Hošek, Jan
Abstract : Our results have shown a positive effect of a mixture of GPs and curcumin on Nrf2/ARE activation. Also, there was an observable increase of the expression of superoxide dismutase 1 (by the mixture) and heme oxygenase 1 (by composites). Abstract : Glucan particles (GPs) from Saccharomyces cerevisiae consist mainly of β-1, 3-d -glucan. Curcumin is a phenolic compound of plant origin. A 24 h incubation with a mixture of GPs and curcumin increased the expression of the Nrf2 protein and increased the activation of the Nrf2–ARE system significantly.